2000
DOI: 10.1159/000045733
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Matrix Metalloproteinase Activity in the Kidneys of Hereditary Nephrotic Mice (ICGN Strain)

Abstract: Abnormalities of extracellular matrix (ECM) metabolism, i.e., overproduction and/or inhibition of ECM breakdown, may contribute to progression of fibrotic degeneration in the kidney. Earlier studies revealed that major ECM components, type I, III, and IV collagens, etc., were accumulated in glomeruli and tubulointerstitium in kidneys of Institute of Cancer Research (ICR) derived glomerulonephritis (ICGN) mice which are a novel inbred strain of mice with a hereditary nephrotic syndrome of unknown etiology and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
63
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(71 citation statements)
references
References 14 publications
(37 reference statements)
6
63
0
Order By: Relevance
“…Our previous studies [2,3,[19][20][21][22][23] and the present findings indicate that the ICGN mouse is a unique model for studying the mechanisms of glomerular injury and renal fibrosis. This is the first report that an enzyme that degrades the ECM contributes to glomerular injury in ICGN mice.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…Our previous studies [2,3,[19][20][21][22][23] and the present findings indicate that the ICGN mouse is a unique model for studying the mechanisms of glomerular injury and renal fibrosis. This is the first report that an enzyme that degrades the ECM contributes to glomerular injury in ICGN mice.…”
Section: Discussionsupporting
confidence: 64%
“…Notably, GBM components are accumulated at the earliest stage of renal fibrosis in the kidneys of ICGN mice [14]. Previously, we demonstrated that low levels of MMPs that degrade ECM components resulted in the renal fibrosis in these mice [20,23]. We found decreased levels of gelatinases (MMP-2, -9), which degrade basement membrane (BM) components such as type IV collagen, and membrane type1 MMP, in the kidneys [20,23], but their expression mainly occurred in renal tubules.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations